2016
DOI: 10.1177/1077559516633304
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare, Juvenile Justice, Mental Health, and Education Providers’ Conceptualizations of Trauma-Informed Practice

Abstract: This study systematically examined child-service providers' conceptualizations of trauma-informed practice (TIP) across service systems, including child welfare, juvenile justice, mental health, and education. Eleven focus groups and nine individual interviews were conducted, totaling 126 child-service providers. Conventional content analysis was used to analyze the qualitative data with interrater reliability analyses indicating near perfect agreement between coders. Qualitative analysis revealed that child-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 36 publications
0
66
0
Order By: Relevance
“…This is a troubling omission given that work-related traumatic stress symptoms are prevalent and associated with impaired job performance among front-line staff (e.g., attorneys, probation/ correctional officers, law enforcement) in the justice system (Denhof & Spinaris, 2013; Levin et al, 2011; Skogstad et al, 2013). Additionally, several groups of justice system professionals have expressed their desire for greater organizational support around these matters (Donisch et al, 2016; Knowlton, 2015; Severson & Pettus-Davis, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…This is a troubling omission given that work-related traumatic stress symptoms are prevalent and associated with impaired job performance among front-line staff (e.g., attorneys, probation/ correctional officers, law enforcement) in the justice system (Denhof & Spinaris, 2013; Levin et al, 2011; Skogstad et al, 2013). Additionally, several groups of justice system professionals have expressed their desire for greater organizational support around these matters (Donisch et al, 2016; Knowlton, 2015; Severson & Pettus-Davis, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The juvenile justice system relative to the education or child welfare systems provides very little mental health resources and support to youth (Farmer, Burns, Phillips, Angold, & Costello, 2003). Research has also qualitatively identified inconsistencies in the delivery of traumainformed mental health care within the juvenile justice settings (Donisch et al, 2016). In fact, the philosophies of treatment for youth involved from the juvenile justice system differ greatly from other systems in that the juvenile justice system is largely focused on culpability and community safety (Maschi et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although trauma exposure is associated with juvenile justice involvement (Abram et al, 2004;Ko et al, 2008), the system has historically ignored trauma or mental health symptomatology in service delivery (Donisch, Bray, & Gewirtz, 2016). To effectively address the needs and improve outcomes for youth in juvenile justice systems, it is essential to recognize, assess, and provide treatment for trauma symptoms (Ko et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to violence exposure, the concept of trauma-informed care within communities and settings at various levels of care is gaining momentum (Hanson and Lang, 2016). Examples include multitiered approaches within schools (Chafouleas et al, 2016), as well as efforts within child welfare, juvenile justice, and mental health systems (Donisch, Bray, and Gewirtz, 2016). However, most of these models have not been evaluated to see whether they do, in fact, produce a more resilient child, family, or community.…”
Section: Future Directionsmentioning
confidence: 99%